2019
DOI: 10.1080/19490976.2019.1595300
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal and hepatic microbiota changes associated with chronic ethanol administration in mice

Abstract: Alcohol-induced liver disease is closely related to translocation of bacterial products and bacteria from the intestine to the liver. However, it is not known whether bacterial translocation to the liver depends on certain intestinal microbiota changes that would predispose bacteria to translocate to the liver. In this study, we investigated the microbiota in the jejunum, ileum, cecum, feces and liver of mice subjected to chronic ethanol feeding using a Lieber DeCarli diet model of chronic ethanol feeding for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 48 publications
0
25
0
1
Order By: Relevance
“…76 Alcohol consumption can increase intestinal bacterial and fungal dysbiosis, which contribute to disease susceptibility, loss of gut barrier function, and progression of liver injury. [77][78][79][80] Mice given antibiotics develop less severe liver injury, and do not have intestinal reductions in occludin expression, with ethanol feeding. 74,81 However, germ-free mice, which lack commensal bacteria, develop more severe ethanol-induced injury than conventionally housed mice (with commensal bacteria).…”
Section: Alcohol-induced Liver Diseasementioning
confidence: 99%
“…76 Alcohol consumption can increase intestinal bacterial and fungal dysbiosis, which contribute to disease susceptibility, loss of gut barrier function, and progression of liver injury. [77][78][79][80] Mice given antibiotics develop less severe liver injury, and do not have intestinal reductions in occludin expression, with ethanol feeding. 74,81 However, germ-free mice, which lack commensal bacteria, develop more severe ethanol-induced injury than conventionally housed mice (with commensal bacteria).…”
Section: Alcohol-induced Liver Diseasementioning
confidence: 99%
“…Increased intestinal permeability is a common feature in preclinical models of ethanol-induced liver disease. 101 In addition, microbial derived products appear to play an important role for ethanol-induced liver disease in mice. Mice with genetic deletions in the LPS signaling pathway are resistant to alcohol-induced liver damage.…”
Section: Bacterial Translocationmentioning
confidence: 99%
“…Moreover, gram-negative Prevotella not only increased in the mucus layer of the ileum but also in liver samples suggesting that translocation of viable bacteria to the liver might be associated with microbiota changes in the distal gastrointestinal tract. 101 Gastric acid suppression by proton pump inhibitor increases intestinal Enterococcus and its translocation to the liver, exacerbating ethanol-induced liver disease both in mice and humans. 103 E. faecalis was detectable in the liver of mice given cytolytic and non-cytolytic E. faecalis and fed an ethanol diet, but not when mice were fed a control diet indicating that ethanol-induced changes in the gut barrier are necessary for the translocation of cytolytic E. faecalis.…”
Section: Bacterial Translocationmentioning
confidence: 99%
“…In patients with AH compared to non-alcohol consuming controls, there was an increase in isoprenoid synthesis through upregulation of the mevalonate and anthranilate degradation, which are known modulators of gram-positive bacterial growth and biofilm production, respectively. Bluemel et al 53 investigated the microbiota in the jejunum, ileum, cecum, feces and liver of mice subjected to chronic ethanol feeding; they found that chronic ethanol administration modified alpha diversity in the ileum and the liver, largely driven by an increase in gram-negative phyla, resulting in endotoxemia. Specifically, the gram-negative Prevotella increased in the mucus layer of the ileum and also in liver tissues, suggesting the central role of dysbiosis and bacterial translocation leading to liver injury with alcohol use.…”
Section: Aldmentioning
confidence: 99%